Targeted basic research to highlight the role of estrogen and estrogen receptors in the cardiovascular system. (May 2017) - Dworatzek, Elke; Mahmoodzadeh, Shokoufeh
Graphical abstract: Similar and distinct effects of estrogen receptor alpha (ERα) and beta (ERβ) under different pathophysiological conditions in male and female mice hearts using ER knock-out and transgenic mouse models. Inhibiting effects mediated by ER are indicated by "−" and promoting effects are indicated by "+". Abstract: Epidemiological, clinical and animal studies revealed that sex differences exist in the manifestation and outcome of cardiovascular disease (CVD). The underlying molecular mechanisms implicated in these sex differences are not fully understood. The reasons for sex differences in CVD are definitely multifactorial, but major evidence points to the contribution of sex steroid hormone, 17β-estradiol (E2), and its receptors, estrogen receptor alpha (ERα) and estrogen receptor beta (ERβ). In this review, we summarize past and present studies that implicate E2 and ER as important determinants of sexual dimorphism in the physiology and pathophysiology of the heart. In particular, we give an overview of studies aimed to reveal the role of E2 and ER in the physiology of the observed sex differences in CVD using ER knock-out mice. Finally, we discuss recent findings from novel transgenic mouse models, which have provided new information on the sexual dimorphic roles of ER specifically in cardiomyocytes under pathological conditions.